Technical skills influences on front crawl tumble turn performance in elite female swimmers - Puel, F.; Hellard, P.; Pyne, D. B.; Morlier, J. (Journal of Sports Science & Medicine, 2023)
The objective of this research was to compare technical skills composed of kinematic and kinetic variables in the complex motor task of a tumble turn between 9 elites and 9 sub-elite female swimmers. The best tumble turn among three attempts was analyzed using a three-dimensional underwater protocol. A total of 37 kinematic variables were derived from a Direct Linear Transformation algorithm for 3D reconstruction, and 16 kinetic variables measured by a piezoelectric 3D force platform. Data were analyzed by Student's t-test and effect size statistics. Pearson correlations were applied to the data of the eighteen swimmers to relate the association of 53 kinematic, kinetic variables to the performance of the tumble-turn (3 meters Round Trip Time, 3m RTT). The approach and the whole turn times were faster for elite swimmers compared to sub elites (1.09±0.06 vs. 1.23±0.08 sec, and 2.89±0.07 vs. 3.15±0.11 sec.), as well as the horizontal speeds of the swimmers` head 1 m before the rotation (1.73±0.13 vs. 1.57±0.13 m/sec.), at the end of the push-off on force platform (2.55±0.15 vs. 2.31±0.22 m/sec.) and 3 m after the wall (2.01±0.19 vs. 1.68±0.12 m/sec.). Large differences (|d| > 0.8) in favor of the elite swimmers were identified for the index of upper body extension at the beginning of the push-off, the lower limb extension index at the end of push-off, and among the kinetic variables, the horizontal impulse and lateralization of the push-off. Correlations for the whole group revealed a moderate to strong relationship between 6 body extension indices and 3mRTT performance. For the kinetic variables, the correlations indicated the fastest swimmers in 3mRTT showed large lateral impulse during placement (r=0.46), maximum horizontal force during the push-off (r=0.45) and lateralization of the push-off (r=0.44) (all p<0.05). Elite female swimmers had higher approach and push-off speeds, were more streamlined through the contact, and showed a higher horizontal impulse and lateralization of the push-off, than their sub-elite counterparts.